Towards appropriate, accessible information networks in developing communities : an assessment of selected information literacy projects and programmes in South Africa and Namibia - Jacobs, Veronica (Library and Information Studies Centre (LISC), 2020)
The central theme of this study revolves around information delivery in a developing community. The notion of appropriate, accessible information networks is scrutinised. The Okavango region in Namibia is used as a case study of a developing, rural community. The region is underdeveloped in important spheres such as health, agriculture and education. Library and related information services are either underdeveloped or undeveloped. The region has a favourable rainfall pattern and a viable agricultural resource base. This is important for Namibia, because the country has large areas of semi-desert and desert. Although the Okavango region is vast ( some 4.6 million hectares), the majority of the population (137,000 at the 1991 census), are settled in a narrow 5-10 kilometre strip along the south bank of the Okavango river. This in itself offers challenging opportunities to improve connectivity and access to appropriate information for community development. The current situation with regard to information delivery and information literacy levels in Namibia is sketched and a detailed description of two projects striving towards appropriate, accessible information delivery given. Both projects are based in a tertiary environment, one at the University of Namibia and the other at five Western Cape tertiary institutions in South Africa. Although, essentially these projects aim at improving information delivery at a tertiary level, community outreach components are woven into the long term vision of both projects. The information literacy components of the projects described are of special significance. The concept of information literacy and the potential of information literacy projects and programmes to facilitate the delivery of appropriate, accessible information to developing communities are probed